Improving prodigiosin production by transcription factor engineering and promoter engineering in Serratia marcescens - Pan, Xuewei; You, Jiajia; Tang, Mi; Zhang, Xian; Xu, Meijuan; Yang, Taowei; Rao, Zhiming (Frontiers in Microbiology, 2022)
Prodigiosin (PG), a red linear tripyrrole pigment produced by Serratia marcescens, has attracted attention due to its immunosuppressive, antimicrobial, and anticancer properties. Although many studies have been used to dissect the biosynthetic pathways and regulatory network of prodigiosin production in S. marcescens, few studies have been focused on improving prodigiosin production through metabolic engineering in this strain. In this study, transcription factor engineering and promoter engineering was used to promote the production of prodigiosin in S. marcescens JNB5-1. Firstly, through construing of a Tn5G transposon insertion library of strain JNB5-1, it was found that the DNA-binding response regulator BVG89_19895 (OmpR) can promote prodigiosin synthesis in this strain. Then, using RNA-Seq analysis, reporter green fluorescent protein analysis and RT-qPCR analysis, the promoter P17 (PRplG) was found to be a strong constitutive promoter in strain JNB5-1. Finally, the promoter P17 was used for overexpressing of prodigiosin synthesis activator OmpR and PsrA in strain JNB5-1 and a recombinant strain PG-6 was obtained. Shake flask analysis showed that the prodigiosin titer of this strain was increased to 10.25 g/l, which was 1.62-times that of the original strain JNB5-1 (6.33 g/l). Taken together, this is the first well-characterized constitutive promoter library from S. marcescens, and the transcription factor engineering and promoter engineering can be also useful strategies to improve the production of other high value-added products in S. marcescens.